Tanggung Jawab Sosial Perusahaan Dalam Rangka Menjaga Keberlangsungan Usaha - Sari Rahayu (CV. ITTC INDONESIA, 2023)
Corporate Social Responsibility (CSR) is a concept that a corporation decides voluntarily to contribute for better society and clearer environment. A corporation could identify its stakeholders and internalize needs and values into strategic decision-making process and corporate’s ethics operation. CSR is one of ethics items in building long term performance. CSR is what should be or what corporation must do for society. By implementing CSR, society will feel secured and CSR is needed to cope vertical and horizontal conflicts. Therefore, CSR could strengthen corporate’s reputation and business sustainability.